2018
DOI: 10.1038/s41598-018-25060-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic differences between focal and diffuse traumatic brain injury in human brain tissue

Abstract: The early molecular response to severe traumatic brain injury (TBI) was evaluated using biopsies of structurally normal-appearing cortex, obtained at location for intracranial pressure (ICP) monitoring, from 16 severe TBI patients. Mass spectrometry (MS; label free and stable isotope dimethyl labeling) quantitation proteomics showed a strikingly different molecular pattern in TBI in comparison to cortical biopsies from 11 idiopathic normal pressure hydrocephalus patients. Diffuse TBI showed increased expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 71 publications
3
43
0
Order By: Relevance
“…Second, in both rats and humans, focal and diffuse brain injuries result in distinct serum miRNA profiles. Although a previous study showed differences in focal and diffuse injuries in living biopsies of human brain tissue 16 , we show here the first evidence that blood miRNA profiles could reflect the heterogeneity and injury-specific pathogenic changes induced in the brain by a diffuse or focal TBI which, at present, are only conclusively identifiable by sophisticated neuroimaging 15 . Given that genetic factors affect the heterogeneous presentation of TBI and functional outcome after TBI 17 , it is notable that discriminating focal from diffuse injuries by principal component analysis is congruent with the diagnosis by CT imaging.…”
Section: Discussionmentioning
confidence: 51%
“…Second, in both rats and humans, focal and diffuse brain injuries result in distinct serum miRNA profiles. Although a previous study showed differences in focal and diffuse injuries in living biopsies of human brain tissue 16 , we show here the first evidence that blood miRNA profiles could reflect the heterogeneity and injury-specific pathogenic changes induced in the brain by a diffuse or focal TBI which, at present, are only conclusively identifiable by sophisticated neuroimaging 15 . Given that genetic factors affect the heterogeneous presentation of TBI and functional outcome after TBI 17 , it is notable that discriminating focal from diffuse injuries by principal component analysis is congruent with the diagnosis by CT imaging.…”
Section: Discussionmentioning
confidence: 51%
“…Another study that used fresh human brain biopsies for MS‐based proteomic analysis showed that there are several proteomic alterations in these brains following TBI. This study also demonstrated that these alterations were more pronounced in patients with widespread axonal injury when compared with focal injury, which may make these severely injured brains more susceptible to secondary insults . While the pathological changes associated with TBI have been studied extensively, a gap in knowledge remains as to how therapeutic interventions, such as VPA, may improve clinical outcomes following TBI.…”
Section: The Emergence Of “Omics” Technologiesmentioning
confidence: 66%
“…Diffuse TBI has shown to increase the expression of peptides related to neurodegeneration, and decrease the expression of peptides related to antioxidant stress like glutathione S‐transferase Mu 3, etc. It has also been shown to increase the expression of potential biomarkers such as neurogranin, fatty acid binding protein, etc . Proteomic approaches are well suited for studying changes following TBI, and they may help identify targets for novel treatments.…”
Section: Tbi Triggers a Genomic And Proteomic Stormmentioning
confidence: 99%
“…The biggest advantage of brain tissue proteomics is the small area of the brain selected for analysis, which allows for a more specific and intuitive understanding of the injury process. Previous studies have revealed that these differentially expressed proteins might be predominantly associated with oxidative damage,[ 11 ] glial cell differentiation,[ 12 ] neurodegenerative processes,[ 13 ] acute phase response,[ 14 ] and complement cascade. [ 15 ]…”
Section: P Roteomics S Tudies In mentioning
confidence: 99%
“…A recent proteomics study from Ganesan's laboratory revealed serum protein biomarkers in patients with mild, moderate, and severe TBI. [ 16 ] Moreover, proteomics technology has been designed to identify possible markers present during the acute[ 13 ] and chronic[ 15 ] TBI phases. Candidate biomarkers for brain injury show their clinical utility in monitoring TBI-associated pathologies and distinguishing the different severity strata.…”
Section: P Roteomics S Tudies In mentioning
confidence: 99%